Internalisasi Nilai-Nilai Moderasi Beragama Melalui Ritual Tahunan Manganan Jepara - Qoirunnisa, Fentika Zahra; Astuti, Nita Yuli (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
This study highlights the increasing discrimination and religious intolerance in Indonesia, which requires awareness of the importance of religious moderation. This research explores the values of moderation in Manganan traditional rituals in Blingoh Village, Jepara, through descriptive qualitative methods with in-depth interviews and documentation studies. The results show that Manganan strengthens societal harmony by highlighting the values of tawassuth (middle attitude) and tawazun (balance). This tradition reflects the principles of Islamic moderation as in the QS. Al-Baqarah: 143, emphasizes tolerance and balance. Eating together (sego katan) strengthens social relations, cooperation and interfaith dialogue. This ritual preserves the values of togetherness and tolerance as a cultural heritage that fosters love and peace in people's lives.